Low barriers, high stakes : formal and informal diffusion of AI in the workplace - Melanie Arntz [Verfasser]; Baum, Myriam [Verfasser]; Brüll, Eduard [Verfasser]; Dorau, Ralf [Verfasser]; Hartwig, Matthias [Verfasser]; Matthes, Britta [Verfasser]; Meyer, Sophie-Charlotte [Verfasser]; Schlenker, Oliver [Verfasser]; Tisch, Anita [Verfasser]; Wischniewski, Sascha [Verfasser] (My University, 2025)
“Artificial intelligence (AI) is diffusing rapidly in the workplace, yet aggregate productivity gains remain limited. This paper examines the dual diffusion of AI – through both formal, employer-led and informal, employee-initiated adoption – as potential explanation. Using a representative survey of nearly 10,000 employees in Germany, we document a high extensive but low intensive margin of usage: while 64 percent use AI tools, only 20 percent use them frequently. This diffusion is strongly skill-biased and depends less on establishment and regional characteristics. While formality is associated with more frequent usage, training, AI-based supervision, and higher perceived productivity gains, it does not broaden access. These patterns suggest that widespread informal usage can coexist with limited productivity effects when complementary investments and organizational integration lag behind.“ (authors’ abstract; BIBB-Doku)
Keywords: G 2.2.1 Technologisierung; 370; Arbeitswelt; Arbeitsplatz; Künstliche Intelligenz; Anwendung; Produktivitätsentwicklung; Arbeitnehmer; Befragung